Family biosocial variables influencing the use of insecticide treated nets for children in Eastern Nigeria - Gabriel U. P. Iloh; Agwu N Amadi; Charles E Obiukwu; Patrick U Njoku; John N Ofoedu; Godwin O. C. Okafor (Wolters Kluwer Medknow Publications, 2013)
Background: Effective reduction of malaria morbidity and mortality in Nigerian children under the age of five depends to a large extent on family biosocial factors. Although, the awareness of insecticide treated bed nets (ITNs) is reportedly high and increasing in Nigeria there remain large gaps between awareness, possession and use by families with children under the age of five in Nigeria. Aim: To determine the family biosocial variables that influence the use of insecticide treated nets for children in Eastern Nigeria. Materials and Methods: A descriptive hospital-based study was carried out from June 2008-June 2011 on a cross-section of 415 mothers with children under the age of five, who were treated for confirmed malaria, and met the selection criteria were interviewed using a pretested, structured researcher-administered questionnaire. The questionnaire tool elicited information on family socio-demographic variables, inter-spousal discussion, communication, concurrence and participation in the use of insecticide treated bed nets; and reasons for non-utilization. The period of usage in the previous 6 months was assessed and graded using a scoring system of 0-4. Scores of 1-4 indicated usage while score of 0 meant non use. Results: The rate of ITNs use was 53.0%. The family variables that significantly influenced utilization were secondary education and above of parents (mother: P0 = 0.009; father: P = 0.001), monogamy (P value = 0.024), family size of 1-4 (P value = 0.016) and parents living together ( P = 0.001); others included parents' occupation (mother: P = 0.003; father: P = 0.04) and inter-spousal discussion (P value = 0.001), communication (P value = 0.001), concurrence ( P = 0.000) and participation ( P = 0.000). The commonest reason for non- use was inconvenience during sleep ( P = 0.04). Conclusion: This study shows that the rate of ITN use was marginally good. Specifically, this rate was significantly influenced by some family variables. The families of children under the age of five should, therefore, be the focus of intensive health promotion campaign to influence the use of ITNs to produce ITN family friendly communities.